Quantitation of yeast cell-cell fusion using multicolor flow cytometry - Salzman, Valentina (2015)
Mating of haploid Saccharomyces cerevisiae cells of opposite sex provides a powerful model system to study the cell-cell fusion. However, a rapid and standardized method is much needed for quantitative assessment of fusion efficiency. The gold standard method relies on counting mating pairs in fluorescence microscopy images. This current method is limited by expectancy bias and it is time consuming, restricting the number of both cell-cell fusion events and strains that can be analyzed at once. Automatic approaches present a solution to these limitations. Here, we describe a novel flow cytometric approach that is able to quickly both identify mating pairs within a mixture of gametes and quantify cell fusion efficiency. This method is based on staining the cell wall of yeast populations with different Concanavalin A-fluorophore conjugates. The mating subpopulation is identified as the two-colored events set and fused and unfused mating pairs are subsequently discriminated by green fluorescent protein bimolecular complementation. A series of experiments was conducted to validate a simple and reliable protocol. Mating efficiency in each sample was determined by flow cytometry and compared with the one obtained with the current gold standard technique. The results show that mating pair counts using both methods produce indistinguishable outcomes and that the flow cytometry-based method provides quantitative relevant information in a short time, making possible to quickly analyze many different cell populations. In conclusion, our data show multicolor flow cytometry-based fusion quantitation to be a fast, robust, and reliable method to quantify the cell-cell fusion in yeast.